Mechanical Properties of Recycled Aggregate Concrete at Low and High Water/Binder Ratios - Gai-Fei Peng; Yan-Zhu Huang; Hai-Sheng Wang; Jiu-Feng Zhang; Qi-Bing Liu (Advances in Materials Science and Engineering)
This paper presents an experimental research on mechanical properties of recycled aggregate concrete (RAC) at low and high water/binder (W/B) ratios. Concrete at two W/B ratios (0.255 and 0.586) was broken into recycled concrete aggregates (RCA). A type of thermal treatment was employed to remove mortar attached to RCA. The RAC at a certain (low or high) W/B ratio was prepared with RCA made from demolished concrete of the same W/B ratio. Tests were conducted on aggregate to measure water absorption and crushing values and on both RAC and natural aggregate concrete (NAC) to measure compressive strength, tensile splitting strength, and fracture energy. The mechanical properties of RAC were lower than those of NAC at an identical mix proportion. Moreover, the heating process caused a decrease in compressive strength and fracture energy in the case of low W/B ratio but caused an increase in those properties in the case of high W/B ratio. The main type of flaw in RCA from concrete at a low W/B ratio should be microcracks in gravel, and the main type of flaw in RCA from concrete at a high W/B ratio should be attached mortar.